EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DAN TEAM ASSISTED INDIVIDUALIZATION DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA POKOK BAHASANGARIS DAN SUDUT DITINJAU DARI SIKAP SISWATERHADAP MATEMATIKA KELAS VII SMP - Maharani, Swasti; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Journal of Mathematics and Mathematics Education, 2014)
Abstract: The objectives of this research were to find out: (1) which learning model of the GI with CTL approach, TAI with CTL approach or conventional learning results in a better learning achievement in mathematics; (2) which students attitudes toward mathematics of the positive, neutral, or negative types results in a better learning achievement in mathematics; (3) in each students attitudes toward mathematics, which learning model of the GI with CTL approach, TAI with CTL approach or conventional learning results in a better learning achievement in mathematics; and (4) in each learning model, which students attitudes toward mathematics of the positive, neutral, or negative types results in a better learning achievement in mathematics. This research used the quasi experimental research method with the factorial design of 3x3. Its population was all of the students in Grade VII of State Junior High Schools in Ngawi regency. The samples of the research were taken by using the stratified cluster random sampling technique. The data of the research were analyzed by using the unbalanced two-way analysis of variance at the significance level of 5%. The results of this study showed that: (1) the GI and TAI with CTL approach learning models result in the same good learning achievement in mathematics, but both result in a better learning achievement in mathematics than the conventional learning model; (2) the mathematics learning achievement with positive attitudes toward mathematics was better than that with neutral and negative attitudes towards matematics, that with neutral attitude towards matematics was better than that with negative attitudes toward mathematics; (3) in each students attitudes toward mathematics type, the GI and TAI with CTL approach learning models result in the same good learning achievement in Mathematics, but both result in a better learning achievement in mathematics than the conventional learning model; (4) in each learning model, the mathematics learning achievement with positive attitudes toward mathematics was better than that with neutral and negative attitudes towards matematics, that with neutral attitude towards matematics was better than that with negative attitudes toward mathematics.Key words: learning model, GI, TAI, conventional, CTL approach, students attitudes toward mathematics.